Comparative safety of antipsychotic medications in elderly stroke survivors: A nationwide claim data and stroke registry linkage cohort study. (July 2021) - Su, Chien-Chou; Yang, Yea-Huei Kao; Lai, Edward Chia-Cheng; Hsieh, Cheng-Yang; Cheng, Ching-Lan; Chen, Chih-Hung; Lin, Huey-Juan; Sung, Sheng-Feng; Chen, Yu-Wei
Abstract: Background: Antipsychotics remain the first choice of treatment for post-stroke psychosis, despite an increased risk of mortality reported in elderly patients. We aimed to compare the mortality risk among antipsychotics in elderly patients with stroke using the stroke registry for external adjustment. Methods: We conducted a retrospective cohort study to identify patients aged above 65 years who were admitted for stroke in the National Health Insurance Database (NHID) from 2002 to 2014. The first date of antipsychotic use after the stroke hospitalization was defined as the index date. Covariates including diseases, medications and external information on smoking, BMI, stroke severity and disability, that were unavailable in the NHID were obtained from the linked Multicenter Stroke Registry (MSR) and used for propensity score calibration (PSC). The main outcome was one-year all-cause mortality. Results: Stroke patients in the NHID prescribed with haloperidol, quetiapine and risperidone numbered 22, 235, 28, 702 and 8 663, respectively. In the PSC-adjusted analyses, haloperidol [adjusted hazard ratio (aHR) = 1.22; 95% CI 1.18–1.27] and risperidone (aHR = 1.31; 95% CI 1.24–1.38) users had a higher mortality risk than quetiapine users. When the dosage was higher than 0.5 defined daily dose (DDD), haloperidol and risperidone users had a significant mortality risk as compared with those taking a lower dose. Conclusions: In post-stroke elderly patients, quetiapine would pose less mortality risk than risperidone and haloperidol at doses higher than 0.5 DDD. When haloperidol or risperidone is indicated, starting with a lower dose is suggested to avoid excess risk. Highlights: Less studies are to compare mortality risk of antipsychotics in elderly stroke. Previous findings were lack of important unmeasured confounders which may be bias. The PSC methods were used in this study to adjusting unmeasured confounders. Haloperidol and risperidone had dose-response relationships with mortality risk. Our findings provide starting with a smaller dose of antipsychotic is warranted.